Prospects of Wind-Diesel Generator-Battery Hybrid Power System: A Feasibility Study in Algeria. (26th August 2013) - Saheb-Koussa, Djohra; Koussa, Mustapha; Said, Nourredine
Abstract : The present work analyses the feasibility of a wind-diesel generator-battery hybrid system. The wind energy resource data are collected from the weather station at the Renewable Energy Development Center of Bouzareah in Algeria. The recorded values vary from 5.5 m/s to 7 m/s at 25 m. The hybrid system analysis has shown that for a household consuming 1, 270 kWh/yr, the cost of energy is 1.205 USD/kWh and produces 2, 493 kWh/yr in which 93% of electricity comes from wind energy. From this study, it is clear that the optimized hybrid system is more cost effective compared to the diesel generator system alone where the NPC and COE are equal, respectively, to 19, 561 USD and 1.205 USD/kWh and 47, 932 USD and 2.952 USD/kWh. The sensitivity analysis predicts that the grid extension distance varies from 1.25 to 1.85 km depending on wind speed and fuel price which indicate a positive result to implement a stand-alone hybrid power system as an alternative to grid extension. In addition to the feasibility of this system, it can reduce the emission of the CO2, SO2, and NO x, respectively, from 4758 to 147, from 9.45 to 0.294, and from 105 to 3.23 kg/yr. Investments in autonomous renewable energy systems should be considered particularly in remote areas. They can be financed in the framework of the National Energy Action Plan of Algeria.